2009
DOI: 10.1016/j.hisfam.2009.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Family in Dutch migration policy 1945–2005

Abstract: This article looks at how and why the concept of 'family' was used in Dutch migration policy in the period between 1945 and 2005. Throughout this period differences were made between migrant women and migrant men. Whereas the migration of men was associated with labour migration, the migration of women was equated with family migration. Migrant women were constructed as wives and mothers (and not as workers). This construction of women was combined with a victimhood discourse in which women were presented as v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 34 publications
0
13
0
1
Order By: Relevance
“…It further created differences between men and women in how policies were applied: religion surfaced more frequently in women's cases. Here, there are also clear similarities to later decades: bending the rules in cases involving women proved easier than changing the rules (Schrover 2009b). In the fourth place, civil servants and others were afraid of publicity.…”
Section: State Of the Art And Contributions To The Literature: Definimentioning
confidence: 83%
See 2 more Smart Citations
“…It further created differences between men and women in how policies were applied: religion surfaced more frequently in women's cases. Here, there are also clear similarities to later decades: bending the rules in cases involving women proved easier than changing the rules (Schrover 2009b). In the fourth place, civil servants and others were afraid of publicity.…”
Section: State Of the Art And Contributions To The Literature: Definimentioning
confidence: 83%
“…Migrant families also found that leaving their biological children behind in the care of others for long periods of time led to debates about so-called 'broken bonds' . In some cases the idea that ties had ceased to exist after years of being apart resulted in the loss of the rights for children to join their families (Benhabib & Resnik 2009: 235;Schrover 2009b).…”
Section: State Of the Art And Contributions To The Literature: Definimentioning
confidence: 99%
See 1 more Smart Citation
“…Several cases at the European Court of Human Rights (ECHR) at Strasbourg ruled in favor of the right to family life, which had a direct impact on border-crossing couples. For example, the ECHR ruled that a Turkish father could not be deported after his divorce and the subsequent loss of his residence rights in the Netherlands if his child continued to reside in the Netherlands without him (Schrover, 2009; see also Schrover & Moloney, 2013, p. 32-33). These debates about binationalism and relationships seemed to be encapsulated in the story of Betty Mahmoody, which was recounted in the 1987 memoir and film Not without my Daughter.…”
Section: Relationships Past and Present: Tropes Of Exclusion Mixingmentioning
confidence: 99%
“…İstihdam alanlarının özellikleri yanı sıra Hollanda, daha başından kadın işçilerin bekâr ve çocuksuz olmaları koşulunu aramakta, ilk dönemlerde yapılan göçmen işçilik sözleşmelerinde Almanya'dakinin aksine gelecek kişilerin ailesi veya yakınlarını getirmesi yasaklanmaktaydı. 28 Oysa Almanya'da göçmen işçi statüsü ile bağımsız olarak gelen kadınların yanı sıra, eşleri ile birlikte veya takiben Almanya'ya gelen kadınlar da, Alman iş pazarına erken bir tarihte dahil olmaya başlamışlardı. Örneğin Almanya'da Türkiye kökenli göçmen işçiler içinde evli kadınların oranı % 29'du.…”
unclassified